Geriatric palliative caregiving among professional caregivers in Metro Manila: Experiences, social factors, and self-assessments - Clamor, Wilfred Luis L. (Animo Repository, 2017)
This study describes the experiences on geriatric palliative care of 12 caregivers in Metro Manila. This study looks on the variation of these experiences based on influencing phenomenon such as work related background, motivations for caregiving, and social support they receive as well as the influence of this experiences on their self-assessment on health identity and life satisfaction. This study used a qualitative-descriptive research design and involved key informant interviews of caregivers as a research method. Informants were selected through a non-probability sampling technique specifically through a purposive-convenient sampling. Based on the results of the study, experiences of geriatric palliative care responses were classified into caregiving practices, challenges, and rewards in caregiving. Caregiving practices are found to be holistic. Caregivers cite various physical, psychological, social, and spiritual health management strategies as caregiving practices. Most rewards and challenges experienced by caregivers are patient or institution based encouragements and burdensome situations. Variation of these experiences is influenced by work related characteristics, motivations for caregiving, and social support received by caregivers. On one hand, caregivers having care delivery provision, intrinsic motivation, and proximal support tends to prefer psychosocial caregiving practices and experience patient based rewards and challenges. On the other hand, caregivers having medical or non-care work background, extrinsic motivation, and institution based support tends to prefer physical caregiving practices and experiences institution based rewards and challenges. The self-assessment on the health identity and life satisfaction is found to be influenced by the experiences on geriatric palliative care. Caregivers doing physical caregiving practice, psychosocial caregiving practice, and experiences patient based rewards and challenges lead to peculiar health identities such as being fit, getting thinner, and being depressed.